Das Tetraevangelium des Ivan Aleksandăr Edition und Untersuchung - Popova, Tanja (Holzhausen, 2017)
The first philological edition of the famous Four Gospels of the Bulgarian tsar Ivan Alexander from 1356 with its later liturgical additions, accompanied by studies on the codicology and palaeography, the tsar's portraits, textual history, lexics, as well as the liturgical synaxarion and calendary (menologion), bibliographies and indices.